Theory and experiment of tribological test methods - Dykha, O.; Staryi, A.; Getman, M.; Fasolia, V. (Problems of Tribology, 2022)
Based on the analysis of the current state of test methods for wear of friction pairs and the need for methods with certain operating conditions, the problem of developing a theory of test methods for wear of friction pairs according to the ball-cylinder scheme was solved, which makes it possible to determine the parameters of wear models and the general characteristics of the wear resistance of materials. It is shown that the type of wear within the range of properties of the friction pair parameters ensures compliance with the basic conditions in contact: materials, lubrication, pressure, speed, temperature, type of movement, and other less significant factors. It has been established that one of the fundamental issues in the development and conduct of wear tests is to take into account the influence of the stationarity of the wear mode at a point. Test methods in steady and unsteady modes (transient mode) are different. The test method should be based on the solution of the contact problem for a friction pair sample-counter-sample. Based on the solution of wear-contact problem for the "ball-cylinder" scheme, a theory has been developed for identifying the parameters of the wear pattern. To solve the inverse problem, a method of approximating function is proposed and implemented. The power approximation of the experimental function after substitution into the resolving equation gives simple expressions for calculating the model parameters. The results obtained make it possible to predict the intensity of wear of tribocouples under given initial operating conditions: according to loads, sliding speed, characteristics of lubricants and structural materials.